Redes sociales y la promoción de sitios turísticos del cantón Baba Provincia de Los Ríos - Alvear Herrera, Kerly Doménica (2021)
The objective of the case study is to analyze the use of social networks to promote tourist sites in the Baba canton, Los Ríos province. Baba according to data from the National Institute of Statistics and Census of 2010 has an approximate population of 39,681 inhabitants, the oldest canton in the province of Los Ríos known for its history, gastronomy and culture prevailing over the years. Currently, tourism has incorporated social networks in tourism promotion, originating tourism 2.0, reaching tourists directly and encouraging them to visit or purchase the different products and services they offer. For the development of the case study, the different types of descriptive, explanatory and bibliographic research were applied. The methods used were quantitative and qualitative that are aimed at detecting statistical data and qualities of an object of study. The online survey carried out among the inhabitants of the Baba canton resulted in a scarce tourist promotion through the use of social networks, an interview was carried out with the owner of the Rock and Straw tourist complex explaining how he carries out the tourist promotion of his establishment.